Tosaka Jun: Problems of Space and Time in the Philosophy of Everydayness - L. B. Karelova (Концепт: философия, религия, культура, 2024)
The article is focused on the analysis of the theory of space and time by the Japanese neoMarxist philosopher Tosaka Jun. Tosaka was one of the first in his country to act as a critic of Western philosophy, whilst also being a follower of one of its directions. The relevance of studying this cultural phenomenon lies in the possibility of supplementing knowledge about Asian philosophies in the context of the ongoing pivot to the East. The empirical basis of the research was a series of Tosaka’s essays written in 1920-30s focused on the problems of space and time, as well as his monograph “Japanese Ideology.” The main methods used in the article were the methods of comparative analysis, discourse analysis, and (based on the analysis of concepts and terms) the techniques of logical and semantic reconstruction of the system of ideas associated with a particular problem. The author sets the goal of investigating the content and features of the interpretation of space and time in Japanese thought of the 20th century using the example of Tosaka’s philosophy in the context of discussing the role of everydayness as an epistemological basis for philosophical teachings. In this regard, the task of identifying the original solutions and approaches of the Japanese thinker was realized, allowing us to consider his legacy a significant part of the historical and cultural process, as well as to understand the significance of his philosophical ideas in modern discussions. Another important task of the study was to determine the paths of transfer and transformation of ideas, in particular, the refraction and critical rethinking of Western concepts in the Japanese intellectual space. As a result, for the first time in scientific literature, a detailed reconstruction of the problems of space and time, based on the entire body of Tosaka’s works is presented. The conclusion is substantiated that by introducing a number of concepts (everyday space, historical time, character, configuration, relevance, etc.) and rejecting traditional Marxist ideas about the linearity of time and the value approach to history, the Japanese philosopher rethought the Marxist philosophy of history from the position of his theory of everyday life and common sense, creating an original model of unequal cycles formed from within the historical whole and possessing internal completeness, and, thus, presented history as a non-linear and uneven process that has not only a temporal but also a spatial dimension.